Respons Santri Terhadap Kitab Risalah Al-Mahid Sebagai Pedoman Haid Santri Di Pondok Pesantren Manbail Futuh, Jenu, Tuban, Jawa Timur - Umi Masrifah (Analisa: Journal of Social Science and Religion, 2010)
A book entitled Risalah al Mahid tells about women fiqh specifically dima’al-mar’ah. It is written by KH.Masruhan from Brumbung Demak CentralJava, in 1956, using Javanese language and Arabic script (pegon). Thisbook aims to teach women about dima’ al-mar’ah. Physically, female studentshaving menstruation, her womb is ready for reproduction. It is as sign forthem not to go to free social intercourse. This menstruation has affectedwomen to comply with ta’abudi aspects. Woman having menstruation isnot allowed reading Qur’an, prayer, I’tikaf, and others. These should beunderstood by female students. This research focuses on response of femalestudents at Pesantren Mambail Futuh Jenu Tuban East Java toward contentand learning process of a book Risalah al-Mahid. Result of the study describesthat their response is quite good. They say that this book can be guidance forstudents with beginning experience of menstruation. They also tell that itis important to study this book. This research recommends that this bookshould be taught at pesantren and other basic educations. Keywords: Respons Santri, Kitab Risalah al-Mahid, Pesantren ManbailFutuh